Differential myelinated and unmyelinated sensory and autonomic skin nerve fiber involvement in patients with ophthalmic postherpetic neuralgia - Truini, Andrea; Haanpaa, Maija; Provitera, Vincenzo; Biasiotta, Antonella; Stancanelli, Annamaria; Caporaso, Giuseppe; Santoro, Lucio; Cruccu, Giorgio; Nolano, Maria (Frontiers in Neuroanatomy, 2015)
Postherpetic neuralgia is a common and exceptionally drug-resistant neuropathic pain condition. In this cross-sectional skin biopsy study, seeking information on the responsible pathophysiological mechanisms we assessed how ophthalmic postherpetic neuralgia affects sensory and autonomic skin innervation. We took 2-mm supraorbital punch skin biopsies from the affected and unaffected sides in 10 patients with ophthalmic postherpetic neuralgia. Using indirect immunofluorescence and a large panel of antibodies including PGP 9.5 we quantified epidermal unmyelinated, dermal myelinated and autonomic nerve fibers. Although skin biopsy showed reduced epidermal and dermal myelinated fiber density in specimens from the affected side, the epidermal/dermal myelinated nerve fiber ratio was lower in the affected than in the unaffected side (p< 0.001), thus suggesting a predominant epidermal unmyelinated nerve fiber loss. Conversely, autonomic skin innervation was spared. Our study showing that ophthalmic postherpetic neuralgia predominantly affects unmyelinated nerve fiber and spares autonomic nerve fiber might help to understand the pathophysiological mechanisms underlying this difficult-to-treat condition.